Exonic Variants in Aging-Related Genes Are Predictive of Phenotypic Aging Status - Breitbach, Megan E.; Greenspan, Susan; Resnick, Neil M.; Perera, Subashan; Gurkar, Aditi U.; Absher, Devin; Levine, Arthur S. (Frontiers in Genetics, 2019)
Abstract Background Recent studies investigating longevity have revealed very few convincing genetic associations with increased lifespan. This is, in part, due to the complexity of biological aging, as well as the limited power of genome-wide association studies, which assay common single nucleotide polymorphisms (SNPs) and require several thousand subjects to achieve statistical significance. To overcome such barriers, we performed comprehensive DNA sequencing of a panel of 20 genes previously associated with phenotypic aging in a cohort of 200 individuals, half of whom were clinically defined by an “early aging” phenotype, and half of whom were clinically defined by a “late aging” phenotype based on age (65-75 years) and the ability to walk up a flight of stairs or walk for 15 minutes without resting. A validation cohort of 511 late agers was used to verify our results. Results We found early agers were not enriched for more total variants in these 20 aging-related genes than late agers. Using machine learning methods, we identified the most predictive model of aging status, both in our discovery and validation cohorts, to be a random forest model incorporating damaging exon variants (CADD > 15). The most heavily weighted variants in the model were within Poly(ADP-ribose) Polymerase 1 (PARP1) and Excision Repair Cross Complementation Group 5 (ERCC5), both of which are involved in a canonical aging pathway, DNA damage repair. Conclusion Overall, this study implemented a framework to apply machine learning to identify sequencing variants associated with complex phenotypes such as aging. While the small sample size making up our cohort inhibits our ability to make definitive conclusions about the ability of these genes to accurately predict aging, this study offers a unique method for exploring polygenic associations with complex phenotypes.